Effects of dietary supplementation of Poria cocos polysaccharides on intestinal barrier, immune function, and growth of Hyla rabbits - Wei, Wen-Yi; Zhou, XIao-Peng; Yang, XIao-Lin; Zong, Ying; Shi, Kun; Li, Jian-Ming; Diao, Nai-Chao; Du, Rui; Zeng, Fan-Li (Frontiers in Veterinary Science, 2025)
IntroductionOptimal rabbit health, which significantly influences growth and development, depends on three key factors: a robust immune system, proper intestinal function, and balanced gut microbiota. Poria cocos polysaccharide (PCP), the primary bioactive component of Poria cocos, exhibits multiple pharmacological properties with demonstrated benefits for animal health.Methods320 Hyla rabbits were randomly allocated to four dietary groups: a control group receiving a basal diet and three experimental groups supplemented with 0.1, 0.2%, or 0.3% PCP. The growth performance of the rabbits was measured on day 21 and day 42. At the end of the experimental period, growth performance was evaluated, and samples of serum, thymus, liver, spleen, kidney, duodenum, cecum, and cecal content were collected. These samples were used to assess serum biochemical parameters, antioxidant capacity, organ indices, immune function, intestinal permeability, intestinal morphology, microbial composition, and short-chain fatty acid (SCFA) concentrations.ResultsThe results showed that the PCP supplementation significantly enhanced growth performance and immune organ indices in Hyla rabbits. Compared with the control group, PCP was able to significantly increase serum levels of total protein (p < 0.05), albumin (p < 0.05), glucose (p < 0.05), total antioxidant capacity (p < 0.05), catalase (p < 0.05), glutathione peroxidase (p < 0.01), Immunoglobulin A (p < 0.05), Immunoglobulin G (p < 0.001), Immunoglobulin M (p < 0.01), and Interleukin-10 (p < 0.01), and down-regulate serum levels of total cholesterol (p < 0.05), triglyceride (p < 0.05), malondialdehyde (p < 0.01), Interleukin-6 (p < 0.05), diamine oxidase, D-lactate, and endotoxin (p < 0.05). And PCP significantly increased villus length (p < 0.05) and villus-to-crypt ratio (p < 0.01), as well as duodenum-related intestinal gene expression (p < 0.05) in the duodenum and cecum, and decreased crypt depth in the duodenum and cecum (p < 0.01). In addition, PCP significantly increased the concentration of short-chain fatty acids and improved the structure of gut microbiota.ConclusionIn conclusion, these data suggest that PCP can be used as a potential tool to enhance growth performance by improving serum biochemistry, antioxidant capacity, immunity, gut barrier function, and gut flora composition in Hyla rabbits.